2022
DOI: 10.1002/hep.32446
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic inflammation elicits production of proinflammatory netrin‐1 through exclusive activation of translation

Abstract: Background and Aims: Netrin-1 displays protumoral properties, though the pathological contexts and processes involved in its induction remain understudied. The liver is a major model of inflammation-associated cancer development, leading to HCC. SEE EDITORIAL ON PAGE 1237 Funding informationRomain Barnault and Ievgeniia Chicherova are recipients of a DevWeCan Labex (Laboratories of Excellence Network, ANR-LABX-061) and Agence Nationale de la Recherche sur le Sida et les Hepatites Virales (ECTZ63958) predoctora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…It has been reported that proteins of the Netrin family play a crucial role during the development of the central nervous system and in various pathologies [ 63 , 64 ]. In particular, the Netrin-1 protein which is the ligand of several apoptosis-inducing dependence receptors is described as a key therapeutic target in many types of cancer and an anti-netrin-1 therapeutic antibody is currently being tested in the clinic [ 14 , 65 , 66 ].…”
Section: Team Workmentioning
confidence: 99%
“…It has been reported that proteins of the Netrin family play a crucial role during the development of the central nervous system and in various pathologies [ 63 , 64 ]. In particular, the Netrin-1 protein which is the ligand of several apoptosis-inducing dependence receptors is described as a key therapeutic target in many types of cancer and an anti-netrin-1 therapeutic antibody is currently being tested in the clinic [ 14 , 65 , 66 ].…”
Section: Team Workmentioning
confidence: 99%
“…In this issue of Hepatology , Barnault et al report that netrin‐1 (NTN1) protein levels are strongly up‐regulated in HepaRG cells and in primary human hepatocytes (PHHs) by exposure to toll‐like receptor ligands Pam3Cys‐Ser‐(Lys)4, Riboxxol, and polyinosinic:polycytidylic acid (poly[I:C]), which are well‐known initiators of acute hepatic inflammation. [ 5 ] In addition, the authors demonstrate that NTN1 expression is regulated posttranscriptionally in both HepaRG cells and PHHs, although by different molecular mechanisms. In HepaRG cells, representing a model of dedifferentiated hepatocytes and of late‐stage CLD, NTN1 transcripts are bound by the RNA‐binding protein Staufen‐1 (STAU1).…”
Section: Figurementioning
confidence: 99%
“…In contrast, NTN1 protein levels are increased after inflammatory stimulation in a STAU1‐independent manner involving total polysome‐based translation of the NTN1 transcript for the final induction of the protein in murine livers and PHHs. [ 5 ] Although the mechanisms of NTN1 induction by inflammatory signaling appear to be molecularly different in dedifferentiated HepaRG cells and PHHs, both converge in the rapid induction of NTN1 secretion. In mouse experiments, poly(I:C) treatment induced NTN1 expression and production of key inflammatory cytokines such as CCL2, CCL3, CCL5, and CCL8.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations